2012
DOI: 10.1099/jmm.0.033688-0
|View full text |Cite
|
Sign up to set email alerts
|

S-Carboxymethylcysteine inhibits adherence of Streptococcus pneumoniae to human alveolar epithelial cells

Abstract: Streptococcus pneumoniae is a major pathogen of respiratory infections that utilizes platelet-activating factor receptor (PAFR) for firm adherence to host cells. The mucolytic agent S-carboxymethylcysteine (S-CMC) has been shown to exert inhibitory effects against infection by several respiratory pathogens including S. pneumoniae in vitro and in vivo. Moreover, clinical studies have implicated the benefits of S-CMC in preventing exacerbation of chronic obstructive pulmonary disease, which is considered to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
1
Order By: Relevance
“…Similar to influenza, targeting the microbe-host interaction could provide novel treatment strategies for pneumococcal disease. One example is S-carboxymethylcysteine (S-CMC) which is a mucolytic agent used in COPD which has been shown to inhibit adherence to both pharyngeal and alveolar epithelia (218,219).…”
Section: Targeting Iav and S Pneumoniae At The Mucosal Barriermentioning
confidence: 99%
“…Similar to influenza, targeting the microbe-host interaction could provide novel treatment strategies for pneumococcal disease. One example is S-carboxymethylcysteine (S-CMC) which is a mucolytic agent used in COPD which has been shown to inhibit adherence to both pharyngeal and alveolar epithelia (218,219).…”
Section: Targeting Iav and S Pneumoniae At The Mucosal Barriermentioning
confidence: 99%
“…Domenech et al reported 80% reduction of pneumococcal biofilms growth with the amidase LytA, and, recently, Sumitomo et al reported that S-carboxymethylcysteine inhibits pneumococcal adhesion to human alveolar epithelial cells [48, 49]. Similarly, Trappetti et al showed that neuraminidase inhibitors DANA (i.e., 2,3-didehydro-2-deoxy-N-acetylneuraminic acid), zanamivir, and oseltamivir inhibit the capacity of pneumococci to form sialic acid-dependent biofilms [50].…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the aliA and aliB genes was achieved by transformation of strain D39 with a linear DNA fragment containing a spectinomycin resistance gene (aad9) flanked by the upstream and downstream sequences of the aliA and aliB genes, as previously reported 46 .…”
Section: Preparation Of S Pneumoniae Mutant Strains and Recombinant mentioning
confidence: 99%